The Arthaśāstra in a transcultural perspective: comparing Kauṭilya with Sun-Zi, Nizam al-Mulk, Barani and Machiavelli - Liebig, Michael; Mishra, Saurabh (Pentagon Press, 2017)
Contributed articles
"This book is the product of a collaborative effort by the Institute for Defence Studies and Analyses, New Delhi; South Asia Institute, Heidelberg University; and Institute of South Asian Studies, National University Singapore"--Front flap
"... two trilateral workshops were held: one in May 2015 at IDSA in New Delhi, and another in February 2016 at ISAS in Singapore ..."--Preface
Includes bibliographical references (pages 264-285) and index
Keywords: Kauṭalya -- Congresses; Kauṭalya -- Arthaśāstra; Sunzi -- active 6th century B.C -- Sunzi bin fa; Niẓām al-Mulk -- 1018-1092; Machiavelli, Niccolò -- 1469-1527; India -- Congresses -- Politics and government -- To 997; Konferenzschrift; Aufsatzsammlung; Sun, Wu / Sunzi bing fa; Arthaśāstra; Niẓām-al-Mulk, Abū-ʿAlī al-Ḥasan Ibn-ʿAlī; Sun, Wu; Machiavelli, Niccolò; Kauṭilya